2006
DOI: 10.1093/bjps/axl025
|View full text |Cite
|
Sign up to set email alerts
|

Natural Selection as a Population-Level Causal Process

Abstract: Recent discussions in the philosophy of biology have brought into question some fundamental assumptions regarding evolutionary processes, natural selection in particular. Some authors argue that natural selection is nothing but a population-level, statistical consequence of lowerlevel events (Matthen and Ariew [2002]; Walsh, Lewens, and Ariew [2002]). On this view, natural selection itself does not involve forces. Other authors reject this purely statistical, population-level account for an individual-level, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
1
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(90 citation statements)
references
References 23 publications
0
82
1
7
Order By: Relevance
“…Metaphysical, in the sense such an analysis tries to identify the nature of evolutionary phenomena prior to or independent from a particular scientific theory that deals with these phenomena. It is in this context that Millstein distinguishes discriminate and indiscriminate sampling processes, as two types of causal processes that are affected or not by phenotypic differences between organisms (Millstein, 2002(Millstein, , 2005(Millstein, , 2006. This is an ontological distinction made without resorting to any conceptual apparatus of evolutionary theory.…”
Section: Causalist Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Metaphysical, in the sense such an analysis tries to identify the nature of evolutionary phenomena prior to or independent from a particular scientific theory that deals with these phenomena. It is in this context that Millstein distinguishes discriminate and indiscriminate sampling processes, as two types of causal processes that are affected or not by phenotypic differences between organisms (Millstein, 2002(Millstein, , 2005(Millstein, , 2006. This is an ontological distinction made without resorting to any conceptual apparatus of evolutionary theory.…”
Section: Causalist Responsesmentioning
confidence: 99%
“…Millstein (2006Millstein ( , 2008 analyzes some case studies where field biologists try to establish causal relationships between fitness on the one hand and phenotypic or genetic characters on the other, in order to confirm their adaptation hypotheses that the traits in questions were formed by selection and not by drift. Another classical example is Andersson (1982)'s field study of sexual selection in which he confirmed tail length of widowbirds affect their mating chance (a surrogate measure of fitness) by experimentally manipulating the phenotype.…”
Section: The Causal Basis Of Fitnessmentioning
confidence: 99%
“…Even if we accept, for the sake of the argument, that there could be a way to make this abstractness compatible with the claim that Price's Equation gives us the deep structure of biological evolution, there remains a problem. The problem is that several authors support the idea that it is possible to give a causal interpretation of the FTNS [50][51]. Indeed, the causal interpretation of the evolutionary principles "shows adaptive evolution as a genuine causal process, where fitness and selection are both causes of evolution" [47, is simply a mathematical tautology whose truth follows from the definition of the terms.…”
Section: Ontic Structural Realism and The Meaning Of Price's Equationmentioning
confidence: 99%
“…There are debates about how, precisely, drift is to be distinguished from selection. Some, for example, argue that selection and drift represent distinct causes (Hodge 1987;Millstein 2006), while others hold that the distinction is best understood in terms of outcomes (Matthen and Ariew 2002;Walsh 2007). But regardless of how one attempts to make this distinction, it is clear that if fitness is understood in terms of realized outcomes only, then the theoretical resources for distinguishing selection and drift do not exist.…”
Section: The Propensity Interpretation Of Fitnessmentioning
confidence: 99%